2015
DOI: 10.1124/dmd.115.065813
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Characterization of Reactive Intermediates of Corynoline

Abstract: Corynoline is a 1,3-benzodioxole-containing isoquinoline alkaloid isolated from Corydalis bugeana Turcz., a traditional herbal medicine. Corynoline has reportedly demonstrated multiple pharmacologic properties. Previous studies have also shown that corynoline induced cytotoxicity and inhibited cytochrome P450 (CYP) enzymes, but the mechanisms of the adverse effects remain unknown. The major objective of the present study was to identify reactive metabolites of corynoline responsible for the cytotoxicity and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Meanwhile, the mean t 1/2 of CRL after oral administration of BER for 7 days was significantly shortened from 0.671 to 0.447 h. Our early study demonstrated that CRL was metabolized to three oxidative products both in vitro and in vivo . The oxidative metabolites included two mono‐catechols (M1 and M2), and one bis ‐catechol (M3), as shown in Scheme (Mao et al, ). Naturally, levels of the three oxidative metabolites of CRL were also monitored for the two groups (Figure b–d).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Meanwhile, the mean t 1/2 of CRL after oral administration of BER for 7 days was significantly shortened from 0.671 to 0.447 h. Our early study demonstrated that CRL was metabolized to three oxidative products both in vitro and in vivo . The oxidative metabolites included two mono‐catechols (M1 and M2), and one bis ‐catechol (M3), as shown in Scheme (Mao et al, ). Naturally, levels of the three oxidative metabolites of CRL were also monitored for the two groups (Figure b–d).…”
Section: Resultsmentioning
confidence: 99%
“…Our early study demonstrated that multiple CYP enzymes, including CYPs1A2, 2C9, 2C19, 2D6 and 3A4 (rCYPs1A2, 2C12, 2C13, 2D2, and 3A1), were involved in the metabolism of CRL (Mao et al, ). We examined the activities of these enzymes in animals after 7 days of pretreatment with BER.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations